Minimum Standards For Design And Construction of Onsite Wastewater Systems - Powell, G. Morgan (My University, 1997)
This publication is in partnership with the Kansas Department of Health and Environment to establish minimum standards for septic tank and lateral fields.
MF2214_1997_11
Keywords: MF2214; Health and Safety; Home and Family; MF